pengaruh variasi jenis arus las SMAW terhadap keretakan hasil pengujian bending dan struktur mikro pada material AISI 1010 - Abidin, Moh. Hasyim Zaenul; Sutarto, Eko (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
This research aims to determine the effect of variations in the type of SMAW welding current on cracks that occur in bending tests and to determine the microstructure due to the influence of variations in the type of SMAW welding current on AISI 1010 material. The testing method carried out to support this research uses the bending test method and microstructure observation. Bending testing is used to determine the strength of the material after it has been welded using various types of welding current, whether cracks occur or not. Microstructural observations were used to determine the microstructure of AISI 1010 before and after welding using AC, DC-, and DC+ polarities. From the results of the welding bending test using AC current is better and does not experience cracks. This is because the ferrite content is higher than pearlite, because ferrite is soft. The shape of the microstructure of the AISI 1010 material which is welded using AC, DC-, and DC+ current types has changed in ferrite and pearlite.